A 3D-printable machine for conics and oblique trajectories. Issue 9 (23rd September 2022) - Milici, Pietro; Plantevin, Frédérique; Salvi, Massimo
Abstract : We propose an original machine that traces conics and some transcendental curves (oblique trajectories of confocal conics) by the solution of inverse tangent problems. For such a machine, we also provide the 3D-printable model to be used as an intriguing supplement for geometry, calculus, or ordinary differential equations classes.